"You are bipolar, and I claim my £5". (19th November 2008) - Adshead, Gwen
Abstract : One of the first things trainee psychiatrists learn is that you cannot make a diagnosis just by observing behaviour. Gwen Adshead takes the BBC to task for attempting such diagnoses on camera